2020
DOI: 10.21203/rs.3.rs-123288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of n.c.a. [188, 189, 191pt] Cisplatin From a Cyclotron-produced n.c.a. 188, 189, 191PtCl42- Complex

Abstract: We developed a novel method for production of no-carrier-added (n.c.a.) [188, 189, 191Pt]PtⅡCl42- from an Ir target material, and then synthesized n.c.a. [*Pt]cis-[PtⅡCl2(NH3)2] ([*Pt]cisplatin) from [*Pt]PtⅡCl42-. [*Pt]PtⅡCl42- was prepared as a synthetic precursor of n.c.a. *Pt complex by a combination of resin extraction and anion-exchange chromatography after the selective reduction of IrⅣCl62- with ascorbic acid. The ligand-substitution reaction of Cl with NH3 was promoted by treating n.c.a. [*Pt]PtⅡCl42-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…radio-cisplatin. 26,27 We found that radio-cisplatin causes severe DNA double-strand break (DSB) without chemical damage. 28 Unfortunately, the small DNA-binding fraction of radio-cisplatin led to a low probability of DSBs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…radio-cisplatin. 26,27 We found that radio-cisplatin causes severe DNA double-strand break (DSB) without chemical damage. 28 Unfortunately, the small DNA-binding fraction of radio-cisplatin led to a low probability of DSBs.…”
Section: ■ Introductionmentioning
confidence: 99%